THE INFLUENCE OF THE VARIATION IN ARCH HEIGHT OF THE MAIN TAYAN BRIDGE ON THE MEMBER FORCES - Lusiana, Lusiana; Elvira, Elvira; Yusuf, Muhammad; Sutandar, Erwin; Supriyadi, Asep (Fakultas Teknik Universitas Tanjungpura, 2023)
The height of the bridge arch significantly impacts the strength and structural efficiency. Research on the height of the Tayan Bridge arch was conducted to determine the values and behaviour of member forces, structural weight, and deflection and to design the optimal arch height geometry. This research involved five variations of the arch height. The bridge structure was modelled using AutoCAD software. Relevant bridge loading data based on the SNI 1725-2016 standard was inputted into AutoCAD for structural design, and then the structure was modelled and analysed using SAP2000. The analysis results provided information on the bridge weight, deflection, and member forces. The analysis results were then compared with the bridge arch height, and this comparison was presented in the form of graphs. From the analysis results, it can be concluded that the bridge arch height has a positive linear relationship with the bridge weight. Tensile and compressive forces exhibit opposite behaviour. Increasing the arch height with constant value results in weight, deflection, and member force variations. Constantly expanding the arch height also does not lead to an increase in the stiffness of the bridge. Structurally, the optimal arch height is 42.134 meters.